PERAN GLOBAL ECOLABELLING NETWORK (GEN) TERHADAP PROGRAM EKOLABEL DI INDONESIA (STUDI KASUS: PERUSAHAAN RAPP) - Dahlia, Cici; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research is trying to explain about the role of Global Ecolabelling Networks (GEN) against Indonesia’s ecolabelling program in 2014. Global Ecolabelling Networks (GEN) is an international non-profit network of third party ecolabelling organizations that encourages and promotes type 1 ecolabelling development across the world.This research is using perspective Constructivism, theory international organizations and also using concept of role and sustainable development. This research is also applying qualitative methods and the data obtained comes from books, journals, documents, articles, internet sites and other sources related to this research.Global Ecolabelling Network as international organizations leaded the standardization of eco-label certification, who corporate with ISO and create standard ISO 14024 series. Indonesia become the member of GEN in 2006, the purpose of joining Global Ecolabelling Network is the Indonesian product can compete with another international product, and to protect an environment. RAPP is a large company that has a production paper in Indonesia and it certificate from program eco-label Indonesia. The role of GEN as an International Organization is as media promoting, as facilitator, as a global standard eco-label, and as media informations.Keywords: Global Ecolabelling Network (GEN), Ecolabelling Program, Indonesia, RAPP